A Rainbow in the Night : the Tumultuous Birth of South Africa. - Lapierre, Dominique (Perseus Books Group, 2009)
In 1652 a small group of Dutch farmers landed on the southernmost tip of Africa. Sent by the powerful Dutch India Company, their mission was simply to grow vegetables and supply ships rounding the cape. The colonists, however, were convinced by their strict Calvinist faith that they were among God's "Elect," chosen to rule over the continent. Their sagabloody, ferocious, and ferventwould culminate three centuries later in one of the greatest tragedies of history: the establishment of a racist regime in which a white minority would subjugate and victimize millions of blacks. Called apartheid.